Ekonomiese ontledingstegnieke : 'n kritiese evaluering (2015)
M.Com. (Economics) === The main purpose of this study was the descriptive analysis and theoretical evaluation of various economic forecasting techniques applicable to a wide variety of forecasting problems. A comprehensive review was given of the basic structure of the techniques (theory and mechanics). their appropriateness ,In different forecasting circumstances, their technical and other limitations, advantages and disadvantages, together with a guide to the better understanding and interpretation of their results. Many of the problem areas related to economic forecasting can be avoided or at least alleviated, by a proper study of the adequacy and other distinguishing characteristics of a specific forecasting methodology. Forecasting accuracy is a major interest of anyone concerned with the future. There are many different ways of saying that the future belongs to those who plan for It best. This Is certainly true in economics as the practice thereof is filled with uncertainties. The topic of this dissertation is, therefore, very relevant In today's modern world. Diagnosis and forecasting have become inevitable with the growth of the" risk factor" In this world. Efforts are constantly made to eliminate, neutralize or at least decrease as far as possible, the risk attendant to this uncertainty by accurately predicting the future values of important variables. The importance and need for improved economic forecasting has, without a doubt, grown tremendously in recent years. The list of forecasting application Is quite lengthy as virtually every important operating decision depends to some extent on a forecast. Probably the simplest definition of forecasting is that it Is a process which has as its objective the explaining and prediction of events or conditions which will occur at some future time. More precisely, economic forecasting attempts to predict the change In Important economic phenomena. The forecast must however not be seen as an end product, but rather as an ongoing process of input In the decision-making process. Forecasting Is both an art and a science, but although II is a form of art it Is not without structure. As with any worthwhile art form. the forecasting process Is definitive and systematic. A number of special tools and techniques can be used In predicting the future " values of economic variables. The objective selection among these forecasting techniques is extremely difficult. The many different types of forecasting methods available can be grouped into two main categories: (i) the qualitative forecasting methods and (II) the quantitative methods.